(3JMaI GdCfGe aj Gdhba Ydi GdgeRI dMeRI hgTGes - (3Ydj Hf YKeGf Hf eMeO Hf CMeO, CHh GdHbGA GdYPQj, hjYQa H (B: (3GHf GdbGUM,J (B801 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO aEfc SCdJfi CjgG GdCN GdUGdM Cf CdNU dc hQbGJ eMJhjI Ydi HYV eSGFd ef HGH hba MeRI hgTGe hSejJgG JMaI GdCfGe ai Gdhba Ydi GdgeR dMeRI hgTGe s
(3BNQgG (B:s
(3eSGdI dEjdGa hQSeg HMPa GdCda GdJi bHdgG GdaGA eSCdI CQCjJ PcQ ai GdCfYGe eSCdI Ef TGfFc PcQ ai GdfSGA hde jcf dg cahkG PcQ ai GdHbQI s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B727s
Keywords: (3GdbQGAGJ hGdJLhjOs